Indicators and Index of Elderly Well-Being to Support an Age–Friendly City - Pipit Festi Wiliyanarti; Hari Basuki Notobroto; Hamidah Hamidah; Erfan Rofiqi (Jurnal Ners, 2020)
Introduction: Increasing the life expectancy of the elderly raises complex problems concerning the life aspects of the elderly, family, community, and government. A well-being indicator for the elderly is needed as a measurement tool to facilitate Indonesian elderly individuals to becoming more prosperous. The purpose of this study was to develop well-being indicators and to formulate the elderly well-being Index.Methods: This study used an explanatory research design with a quantitative approach. In total, 400 respondents were collected using multistage random sampling. The physical well-being variable used the Mini-Mental State Examination (MMSE) instrument, Barthel’s index, and the Disease Complaint questionnaire. In addition, a psychology and social well-being instrument, social well-being instrument, and spiritual instrument were employed. Confirmatory Factor Analysis was used to verify the factor structure of all of the observed variables.Results: The results showed that the indicators for elderly well-being are demographic with the following factor loading: (λ) 0.32, social environment (λ)=0.51, health services (λ)=0.55, physical well-being (λ=0.36 psychological well-being (λ)=0.46, social well-being (λ)=0.45 and spiritual well-being (λ)=0.50. The indicators and index can be used as an effort to drive the program, so then the elderly can become productive, prosperous, and meaningful.Conclusion: The elderly well-being index is expected to be a programmatic instrument that can measure and evaluate the welfare of the elderly. This will increase the elderly health program that is available to achieve more holistic well-being and an age-friendly city.